2013
DOI: 10.1136/bcr-2013-008829
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous sclerosing haemangiomas of the lung: an unusual presentation of a rare tumour

Abstract: Pulmonary sclerosing haemangioma  is a rare lung tumour with a preponderance for Asian oriental women. Typically a well-circumscribed, solitary lesion with benign characteristics, there are concerns of malignant potential including regional lymph node metastases. Four histological subtypes exist. Diagnosis can be challenging as patients are usually asymptomatic and radiological findings are non-specific. Surgical resection alone is diagnostic and therapeutic. We present a case of this rare tumour with an uncom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
1
0
1
Order By: Relevance
“…Es bien circunscrita, usualmente solitaria y se ubica en parénquima periférico (4). Hay escasos reportes de crecimiento endobronquial (10, 11) y de lesiones múlti-ples y/o bilaterales (12)(13)(14)(15). La TAC y el PET scan no son específicos, pudiendo en algunos casos sugerir metástasis (16)(17)(18)(19)(20).…”
Section: Discussionunclassified
“…Es bien circunscrita, usualmente solitaria y se ubica en parénquima periférico (4). Hay escasos reportes de crecimiento endobronquial (10, 11) y de lesiones múlti-ples y/o bilaterales (12)(13)(14)(15). La TAC y el PET scan no son específicos, pudiendo en algunos casos sugerir metástasis (16)(17)(18)(19)(20).…”
Section: Discussionunclassified
“…3 Chu et al also described a case in which the sclerosing pneumocytomas were initially misdiagnosed as pulmonary adenocarcinomas. 8 Furthermore, Goel et al reported a case of a young girl in whom sclerosing pneumocytoma was initially mistaken for pulmonary tuberculosis. 9 Typically, sclerosing pneumocytomas are solitary, well-circumscribed lesions of 10-20 mm; however, size may vary.…”
Section: Case Reportmentioning
confidence: 99%